2014
DOI: 10.1370/afm.1703
|View full text |Cite
|
Sign up to set email alerts
|

Program Director Turnover

Abstract: 482the innovative work by individual family physicians such as Jeff Brenner from Camden, New Jersey, who has demonstrated how health care costs can be cut by finding community "hot spots" where emergency departments are over-utilized. 9 We commend the Association of American Medical Colleges (AAMC) for publishing their report on how academic medical centers of the future must be system-based to survive. 9In a recently published report, the AAMC describes 4 options for academic medical centers to move toward a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…31 Administrative pressures contribute to the 12%-14% program director turnover per year in family medicine and median program director tenure of 4-5 years. 26,32 Allowing program directors the flexibility to share nonclinical responsibilities may reduce burnout. The task force concluded that provision of additional protected nonclinical time program directors can assign to themselves or distribute to their associate program directors is needed to complete the additional work encountered in residency programs with a greater number of residents (Table 3).…”
Section: Recommendation 2: the Associate Program Director Must Have A Minimum Of 04 Fte Protected Nonclinical Time To Devote To The Adminmentioning
confidence: 99%
“…31 Administrative pressures contribute to the 12%-14% program director turnover per year in family medicine and median program director tenure of 4-5 years. 26,32 Allowing program directors the flexibility to share nonclinical responsibilities may reduce burnout. The task force concluded that provision of additional protected nonclinical time program directors can assign to themselves or distribute to their associate program directors is needed to complete the additional work encountered in residency programs with a greater number of residents (Table 3).…”
Section: Recommendation 2: the Associate Program Director Must Have A Minimum Of 04 Fte Protected Nonclinical Time To Devote To The Adminmentioning
confidence: 99%
“…PD participation in a leadership and management skills fellowship may improve program quality. 4 Surveys show many PDs plan to step down in the next 1 to 2 years 5,6 and burnout may be a factor. 6,7 Between 11% and 14% of residency programs across specialties have at least one PD change annually.…”
mentioning
confidence: 99%
“…8 Some hypothesize that short average tenure of a PD may limit the strength of residency programs. 5,9 While published articles have commented on PD tenure, 1,2,5 and noted the "short life span," 2 PD tenure has not been rigorously studied and no study has tracked change in tenure over time.…”
mentioning
confidence: 99%